The Oligarch Rewriting Machiavelli's The Prince for Our Time - Sherry, James (Springer International Publishing, 2018)
"Admirers of Machiavelli's ideas and style will enjoy this slim and provocative book which addresses a topic dear to the Florentine secretary: the role of elites in society and politics. James Sherry adds a new twist by taking account of the work of twentieth century 'Machiavellians' such as Gaetano Mosca, early James Burnham, as well as the networks described by ecologists. The result is a smart and ironic view of the contemporary networks of oligarchs, in business as well as in politics and society. Readers interested in such different topics as populism, corporate business, high-level politics and the inevitable Donald Trump will find food for thought-accompanied by Machiavellian wit." -Giovanni Giorgini, Professor of Political Theory, University of Bologna, Italy and Princeton University, USA "500 years after Machiavelli, James Sherry offers us a modern [and wide-ranging] treatise on the oligarchs who now rule our world and how they gain and maintain power. One wonders if the pejorative "Sherryan" will be hurled at the power plays of future oligarchs." -Jeff Cohen, Director, Park Center for Independent Media, Ithaca College, USA This book was written from an earlier text, Machiavelli's The Prince, to show how changes in thinking and in governance work by divergence rather than by romantic revolution or vulgar principles of evolution. The assumptions around change of form are reflected in the way the prior text relates to and diverges from the current book. This notion, derived from theoretical environmentalism and systems analysis, makes change easier to understand and requires fewer contortions than some of the received theories of political systems that pit the rulers against the people, failing to show how conflict of interest among leading cadres is the primary driver of political events. James Sherry is the author of 12 books of criticism and poetry, most recently Oops! Environmental Poetics (2013) and Entangled Bank (2016). He is the editor of Roof Books, a literary press (roofbooks.com) in New York City, USA.